The transformed function is y = 1/3(log(x/3 + 4)) + 1
<h3>How to transform the
logarithmic function?</h3>
The parent logarithmic function is
y = log(x)
When shifted left by 4 units, we have:
y = log(x + 4)
When shifted up by 3 units, we have:
y = log(x + 4) + 3
When compressed vertically by 1/3, we have:
y = 1/3(log(x + 4) + 3)
This gives
y = 1/3(log(x + 4)) + 1
When stretched horizontally by 3, we have:
y = 1/3(log(x/3 + 4)) + 1
Hence, the transformed function is y = 1/3(log(x/3 + 4)) + 1
<h3>The transformation of function f(x)</h3>
We have:
f(x) = log[-(x – 5)] + 4
Set the radicand greater than 0
-(x - 5) > 0
Divide by -1
x - 5 < 0
Add 5 to both sides
x < 5 -- this represents the domain
A logarithmic function can output any real number.
So, the range is ![-\infty < f(x) < \infty](https://tex.z-dn.net/?f=-%5Cinfty%20%3C%20f%28x%29%20%3C%20%5Cinfty)
In the domain, we have:
x < 5
This means that the interval of decrease is ![-\infty < x < 5](https://tex.z-dn.net/?f=-%5Cinfty%20%3C%20x%20%3C%205)
Rewrite as an equation
x = 5 --- this represents the equation of asymptote
Read more about logarithmic functions at:
brainly.com/question/12708344
#SPJ1